The Effect Of Extra And Intra-Campus Organizational Communications On Public Speaking Ability Among Students Of The Faculty Of Social Sciences UINSU - Fadli, Muhamad; Harahap, Nursapia; Susanti, Neila (Pena Cendekia Insani, 2022)
This study aims to determine how the influence of organizational communication in extra and intra-campus on students' public speaking skills . The research was conducted using quantitative research methods . The population used were students of the 2018 Stambuk Communication Science Department as many as 361 people at the State Islamic University of North Sumatra (UINSU) Medan , and using a purposive sampling technique , with the slovin formula with an error rate of 10% and the sample being studied was 79 respondents. through the distribution of questionnaires. The results of this study on the t test stated that organizational communication has a t count> T table (97.34 > 1.99125) with a significance level (0.05), then H0 is Rejected and Ha Accepted, meaning that communication extra and intra-campus organization affect the ability of public speaking students.